Ultra‐Widefield Imaging for Pediatric Retinal Disease. Issue 3 (May 2018) - Patel, Chetan Kantibhai; Buckle, Miranda
Abstract : Abstract: : This article explores the development of retinal imaging, with particular emphasis on ultra‐widefield imaging and the key concept of field of view. Two ultra‐widefield imaging platforms are examined in detail—Optomap and Spectralis—noncontact imaging systems that include protocols for performing angiography in infants. Applications of ultra‐widefield imaging are illustrated using case studies, including diagnosis, monitoring, and screening.